Multi-Screen Interaction Technologies on Internet Streaming Video - Zheng Wei; Weijia Shi; Guqiao Zhu (Dianxin kexue)
Some recent developments in different multi-screen interaction technologies that were used on internet streaming video industry were presented, several multi-screen interaction technologies such as DLNA、Miracast were introduced. The characteristic of these technologies were discussed, and their differences were compared. The new technologies of interaction in internet streaming video were introduced and an overview over the different technologies, standardization activities and the development trend were provided.